Golden Hour: The importance of skin-to-skin contact in the first postpartum hour: an integrative literature review (Research, Society and Development, 2023)
This article aims to know the positive points and the difficulties about the "Golden hour" practice. Its methodology is classified as an integrative literature review study, by means of a bibliographic search made in the databases Latin American and Caribbean Literature on Health Sciences (LILACS), Virtual Health Library (VHL) and Scientific Electronic Library Online (SciELO). Eight articles were selected, portraying observational studies with thematic pertinence to the subject of this study, published in Portuguese in the last 10 years. It was concluded that skin-to-skin contact between mother and baby during the "Golden hour" is important to strengthen bonds, promote breastfeeding, and reduce neonatal morbidity and mortality. It is also emphasized the need for the team's knowledge to verify which interventions with the mother and baby can be postponed in order to promote contact during the "Golden hour".